Workplace Well-Being, Mental Health, Generation Z Performance: A Systematic Review and Future Research Agenda - Elfa Fitria Anabila; Sophia Insan Kamila Armunanto; Ahyar Yuniawan; Intan Ratnawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The increasing participation of Generation Z in the workforce has raised concerns regarding the influence of workplace well-being and mental health on employee performance in modern organizations. This study analyzed the relationship between workplace well-being, mental health, and the performance of Generation Z employees through a systematic review of the academic literature for the period 2019–2026. Using the Systematic Literature Review (SLR) method, this study examined and synthesized relevant scholarly publications to identify key patterns, relationships, and research gaps. The results showed that mental health has a significant positive impact on performance, which is mediated by factors of work-life balance, employee attachment, and psychological security under organizational support. Despite this, a paradoxical phenomenon was discovered in which happiness is not always directly proportional to productivity. Current research gaps indicate the need for further deepening of technology and the integration of these three main variables into a Special Research model for Generation Z. As a practical implication, organizations must adopt flexible Human Resource strategies and inclusive leadership to create a work ecosystem that supports mental health while optimizing employee performance sustainably and comprehensively in the future.